Rapport au temps et orchestration des temporalités en formation - Renàta Varga (Centre National d'Enseignement à Distance, 2013)
This contribution presents a summary of discussions held in a workshop which was devoted to time management in training and gathered practitioners, researchers and experts in distance learning courses. The difficulties for both learners and trainers to manage their time have been reviewed with a view to sharing solutions which have been experienced. The personal history of individuals highlights the key role played by people's psychological ability to manage fragmented timing and shows that the way people relate to time implies more widely the way people relate to themselves and to their environment.